Menilik Pengelolaan Keuangan Generasi Z di Kulon Progo: Pengaruh Literasi, Gaya Hidup, dan Teknologi - Kasbani, Wathur; Prasetyo, Tri Utomo (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze the influence of financial literacy, hedonistic lifestyle, and fintech payment on personal financial management of Generation Z in Kulon Progo Regency. The sampling method in this study used a non-probability sampling method with a purposive sampling technique, involving 85 Generation Z respondents. Data analysis used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that financial literacy and fintech payment partially have positive and significant effects on personal financial management of Generation Z in Kulon Progo Regency, while hedonistic lifestyle has a negative and significant effect. Among these three variables, financial literacy has been shown to be the most dominant factor in influencing personal financial management among Generation Z in Kulon Progo Regency.